Gene Expression Patterns for Proteins With Lectin Domains in Flax Stem Tissues Are Related to Deposition of Distinct Cell Wall Types - Petrova, Natalia; Nazipova, Alsu; Gorshkov, Oleg; Mokshina, Natalia; Patova, Olga; Gorshkova, Tatyana (Frontiers in Plant Science, 2021)
The genomes of higher plants encode a variety of proteins with lectin domains that are able to specifically recognize certain carbohydrates. Plants are enriched in a variety of potentially complementary glycans, many of which are located in the cell wall. We performed a genome-wide search for flax proteins with lectin domains and compared the expression of the encoding genes in different stem tissues that have distinct cell wall types with different sets of major polysaccharides. Over 400 genes encoding proteins with lectin domains that belong to different families were revealed in the flax genome; three quarters of these genes were expressed in stem tissues. Hierarchical clustering of the data for all expressed lectins grouped the analyzed samples according to their characteristic cell wall type. Most lectins differentially expressed in tissues with primary, secondary, and tertiary cell walls were predicted to localize at the plasma membrane or cell wall. These lectins were from different families and had various architectural types. Three out of four flax genes for proteins with jacalin-like domains were highly upregulated in bast fibers at the stage of tertiary cell wall deposition. The dynamic changes in transcript level of many genes for lectins from various families were detected in stem tissue over the course of gravitropic response induced by plant gravistimulation. The data obtained in this study indicate a large number of lectin-mediated events in plants and provide insight into the proteins that take part in tissue specialization and reaction to abiotic stress.